Regime complexity as an asset?: The negotiations of the Arms Trade Treaty - Panke, Diana; Friedrichs, Gordon (Journal of global security studies, 2023)
The Arms Trade Treaty (ATT) is an important milestone in reducing the illicit trade of arms but was highly unlikely to be negotiated and passed. Major powers and states exporting and importing arms were not keen on universally binding regulations, leading to political stalemate in the initial negotiation arena, the Conference on Disarmament. This article investigates under which conditions regime complexity had a positive influence on the ATT negotiation dynamics and result. We distinguish between two types of regime complexity, each providing states with a distinct window of opportunity during international negotiations: horizontal regime complexity can allow states to overcome negotiation gridlock by changing the institutional conditions for passing an agreement. Vertical regime complexity can allow regional organizations to turn into agents of change by bringing in experiences gained on the regional level to the international negotiation table. Our empirical analysis of the ATT negotiations revealed critical scope conditions under which both forms of regime complexity function properly, allowing the negotiations to overcome negotiation gridlock and resulting in the passing of the accord beyond a lowest common denominator. The article contributes to the rich and vibrant scholarship in regime complexity and global governance complexes by making a novel analytical distinction between horizontal and vertical regime complexity and by identifying the opportunity structures under which regime complexity can have positive effects on the negotiation and outcome of international treaties.
Literaturverzeichnis: Seite 13-17
Keywords: Arms Trade Treaty -- 2013 April 02